Civil Servant Performance Appraisal System in Girian District, Bitung City - Mangelep, Sony Alexey; Lumingkewas, Lexi; Pangkey, Itje (Technium Social Sciences Journal, 2023)
Timely Feedback and Coaching and effective coaching are essential to help employees improve their performance. This study aims to find out what obstacles are faced in preparing or making employee performance targets. Growing awareness and better understanding of the importance of evaluating the performance of Civil Servants (PNS) in an effective and sustainable manner in the District of Girian and how the performance of PNS is seen from work productivity which has basic dimensions, namely Attitude, Ability and Work Spirit. The method used is a qualitative research method. The research location is the Girian District Office, Bitung City, with the focus of the research, namely the Performance Assessment System for Civil Servants (PNS) of Girian District, Bitung City. The results of this study indicate that 1) From the attitude aspect, the performance of the District Civil Servants is good, they are able to communicate well with the community; 2) From the aspect of Capability, the performance of District Civil Servants is still lacking; 3) From the aspect of work enthusiasm, the performance of district civil servants is still minimal. The factors that hinder the performance of civil servants in the District of Girian are 1) work motivation is still lacking, so that it can affect the community in community involvement in community activities; 2) Did not receive training and development so that the District Civil Servants did not know what to do when they were appointed as District Civil Servants; 3) The average age of the District Civil Servants is 50 years; 4) Existing regulations change rapidly; 5) Technical agencies are still minimal in providing socialization regarding the latest regulations.